Microparticles in nasal lavage fluids in chronic rhinosinusitis: Potential biomarkers for diagnosis of aspirin-exacerbated respiratory disease - Takahashi, Toru; Kato, Atsushi; Berdnikovs, Sergejs; Stevens, Whitney W.; Suh, Lydia A.; Norton, James E.; Carter, Roderick G.; Harris, Kathleen E.; Peters, Anju T.; Hulse, Kathryn E.; Grammer, Leslie C.; Welch, Kevin C.; et al. (Journal of allergy and clinical immunology, 2017)
Microparticles (MPs) are submicron-sized shed membrane vesicles released from activated or injured cells and are detectable by flow cytometry. MP levels have been used as biomarkers to evaluate cell injury or activation in patients with pathological conditions. We sought to compare MP types and levels in nasal lavage fluids (NLFs) from controls and patients with chronic rhinosinusitis without nasal polyps (CRSsNP), chronic rhinosinusitis with nasal polyps (CRSwNP), and aspirin-exacerbated respiratory disease (AERD). We collected NLFs from patients with CRSsNP (n = 33), CRSwNP (n = 45), and AERD (n = 31) and control (n = 24) subjects. Standardized flow cytometry methods were used to characterize the following MP types: endothelial MPs, epithelial MPs (epithelial cell adhesion molecule [EpCAM](+)MPs, E-cadherin(+)MPs), platelet MPs (CD31(+)CD41(+)MPs), eosinophil MPs (EGF-like module-containing mucin-like hormone receptor-like 1[EMR1](+)MPs), mast cell MPs (high-affinity IgE receptor [FcεRI](+)c-kit(+)MPs), and basophil MPs (CD203c(+)c-kit(−)MPs). Basophil activation was evaluated by the mean fluorescence intensity of CD203c on basophil MPs. Activated mast cell MPs (CD137(+) FcεRI(+)c-kit(+)MPs) were significantly increased in NLFs of controls compared with NLFs of patients with CRSsNP (2.3-fold; P < .02), CRSwNP (2.3-fold; P < .03), and AERD (7.4-fold; P < .0001). Platelet MPs (3.5-fold; P < .01) and basophil MPs (2.5-fold; P < .05) were increased only in patients with AERD. Mean fluorescence intensity of CD203c on MPs was increased in patients with CRSwNP (P < .002) and AERD (P < .0001), but not in patients with CRSsNP. EpCAM(+)MPs in patients with CRSwNP were no different from control (P = .91) and lower than those in patients with CRSsNP (P < .02) and AERD (P < .002). Based on released MPs, mast cells, platelets, and basophils were more highly activated in patients with AERD than in patients with CRS. Epithelial injury was lower in patients with CRSwNP than in patients with CRSsNP and AERD. MP analysis may help identify phenotypes of CRS, and in distinguishing AERD from CRSwNP.